Analisis efektivitas vaksin booster pada kasus terkonfirmasi positif Covid-19 menggunakan uji Mann-Whitney - Ulya, Fadilla Zundina; Dewi, Atika Ratna; Winesti, Alifia Zahra; Nurlita, Laksmi Dyah (Jurusan Matematika FMIPA Universitas Jember, 2023)
Covid cases in Indonesia have started to decline since the vaccination program was carried out in January 2021. Until now the vaccination program in Indonesia has reached the third vaccination stage or booster vaccine. The booster vaccine aims to strengthen the vaccine dose that has been given previously, with the hope of reducing the number of confirmed patients with the Covid-19 virus. To determine the effectiveness of the booster vaccine in reducing the number of Covid-19 in Indonesia, it is necessary to conduct research using the Mann-Whitney non-parametric trial method. This journal will discuss the analysis of the effectiveness of the third dose (booster) vaccine using the Mann-Whitney test. The data collection used is data on the number of patients confirmed positive for Covid before the booster vaccine, namely from July to December 2021 and the number of patients confirmed positive after the booster vaccine from February to July 2022. Whitney manually is 15 while the p-value value in the calculation of Mann Whitney with SPSS is 0.631. The results of calculations provide a conclusion that the third dose vaccination (booster) is not effective in the reducing the number of patients of covid-19 confirmed for the Covid-19.Keywords: Covid-19, Vaccines, Mann Whitney testMSC2020: 62G05, 62G10